Geological storage of CO2 in sub-seafloor basalt: the CarbonSAFE pre-feasibility study offshore Washington State and British Columbia. (July 2018) - Goldberg, David; Aston, Lara; Bonneville, Alain; Demirkanli, Inci; Evans, Curtis; Fisher, Andrew; Garcia, Helena; Gerrard, Michael; Heesemann, Martin; Hnottavange-Telleen, Ken; Hsu, Emily; Malinverno, Cristina; et al.
Abstract: The CarbonSAFE Cascadia project team is conducting a pre-feasibility study to evaluate technical and nontechnical aspects of collecting and storing 50 MMT of CO2 in a safe, ocean basalt reservoir offshore from Washington State and British Columbia. Sub-seafloor basalts are very common on Earth and enable CO2 mineralization as a long-term storage mechanism, permanently sequestering the carbon in solid rock form. Our project goals include the evaluation of this reservoir as an industrial-scale CO2 storage complex, developing potential source/transport scenarios, conducting laboratory and modeling studies to determine the potential capacity of the reservoir, and completing an assessment of economic, regulatory and project management risks. Potential scenarios include sources and transport options in the USA and in Canada. The overall project network consists of a coordination team of researchers from collaborating academic institutions, subcontractors, and external participants. Lessons learned from this study at the Cascadia Basin location may be transferrable elsewhere around the globe.